DAMPAK KARAKTERISTIK INFORMASI SISTEM AKUNTANSI MANAJEMEN PADA KINERJA MANAJERIAL - MARETA CHRISNA GOZALI (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Management accounting system (SAM) provides information for managers to predict consequences that may occur from a variety of alternative activities on the Organization and provides a mechanism for controlling the organization. The purpose of this discussion is to discuss “the impact of information on the performance characteristics of the SAM and discusses the benefits of systems of managerial accounting for managers”. Information that has the characteristics of a good, as broadscope, timeliness, aggregation, and integration it needs to improve the accuracy of decision-making. Performance management would be good if the right management decisions. Both are information can be obtained from the information system of directional and well-integrated, SAM.